Internet Entrepreneurship Psychology for College Students and Internet Financial Crimes Prevention - Li, Ruihua (Frontiers in Psychology, 2022)
This work aims to study the entrepreneurial intention of college students’ Internet Entrepreneurship and the potential risk of Internet financial crime from a psychological perspective. Here, the relevant psychological theories are used to analyze the personal and social factors of College Students’ Internet Financing Entrepreneurship. Specifically, College Students’ Internet Financial Entrepreneurship factors are examined alongside the excellence and feasibility of Internet Entrepreneurship. Secondly, it introduces the main types of Internet financial crimes and analyzes the psychological traits of college students’ Internet financial crimes. Further, the research reveals the possibility of college students committing Internet financial crimes by investigating the current situation of College Students’ Internet Entrepreneurship through a questionnaire survey. The results show that 78% of the respondents have studied college Innovation and Entrepreneurship Education (IEE). More than 90% are interested in entrepreneurship, but most have not undertaken entrepreneurship. Therefore, the current college students’ enthusiasm for Internet Financial Entrepreneurship is affected by many factors and is not high. Finally, given the existing problems, hierarchical nesting prevention measures are proposed to prevent college students’ Internet financial crimes during entrepreneurship. This work provides a reference for analyzing the psychological factors of College Students’ Internet Financial Entrepreneurship and preventing potential Internet financial crimes.